Recent Study on Hard to Machine Material – Micromilling process - Ainur Munira, Rosli; Ahmad Shahir, Jamaludin; Mohd Nizar, Mhd Razali (Transdisciplinary Research and Education Center for Green Technologies, Kyushu University, 2021)
This paper presents an overview of the modern advancement of micromilling as pertained to the machining process from recent research and advancement perspective. The review starts by displaying the characteristics and micromilling contributions background, and later sets up the reader to difficult-to-cut materials. However, the fabricating process usually becomes complicated owing to these material’s unique metallurgical properties. This paper brings to focus the micromilling of difficult-to-cut materials, especially materials that are currently the highlights of various industries. The discussion of research and attributes of difficult-to-cut materials are covered in further detail, which serves with opportunities for future developments.